Aspectos da interação entre Vaccinia virus e célula hospedeira: significado funcional desempenhado pelas MAPKs JNK e ERK na biologia viral - Anna Carolina Toledo da Cunha Pereira (2007)
Intracellular signaling events represent an essential role on virus biology. In recent publications, the Grupo de Transdução de Sinal of Laboratório de Vírus demonstrated that the activation of the protein kinase activated by mitogens (MAPK) (ERK1/2) and their substrates are essential to Vaccinia virus (VACV) multiplication (Magalhães et al, 2001, Andrade et al, 2004, Silva et al, 2006). At this work we analyze the kinetic of activation of MAPKs ERK1/2 and JNK1/2 and their transcript factors during VACV infection. Our results showed that ERK1/2 and JNK1/2 regulate temporally transcript factor c-Jun activation. This interaction MAPKs–c-Jun leads to the formation of DNA-proteins complexes of the sequences AP-1 and CRE in distinct moments of viral infection. We also observed that JNK1/2 activation is mediated by MAPKKs MKK4 and MKK7 and that the VACV growth factor (VGF) participates but it is not essential to this process. Moreover, the viral kinase protein B1R does not participate in activation JNK1/2. To determine the JNK1/2 role in the VACV multiplication, we used the inhibitor SP600125 and it was observed a significant decrease at the viral gene kinase timidin expression, DNA replication, viral protein expression and VACV titles. Despite of these observations, we can not attribute them to JNK1/2 activation because we had different results when utilized knockout cells to these kinases. So we concluded that SP600125 inhibits non-specifically other signaling pathways than that of JNK1/2 which are also important to viral biology. However JNK1/2 does not have a role at viral multiplication, knockout cells to these kinases presented a reduced viral plaque size when compared to wild cells. In JNK1/2 absent we observed an increased EEV release. This fact together with literature relates, allow us to hypothesis that JNK1/2 may have a role on the CEV and EEV release. And also JNK1/2 seems to have a role on the host antiviral response through of IL-6 cytokine induction. Modulation of the signaling pathways MEK/ERK and MKK/JNK during VACV infection correlates with the VACV temporal needing. While MEK/ERK is involved with viral multiplication, MKK/JNK is related with the egress of both viral forms CEV and EEV of the infected cell.